Distance Learning Effects Among Italian Children and Parents During COVID-19 Related School Lockdown - Crisci, Giulia; Mammarella, Irene C.; Moscardino, Ughetta M. M.; Roch, Maja; Thorell, Lisa B. (Frontiers in Psychiatry, 2021)
During the COVID-19 pandemic, both children and their parents experienced consequences related to distance learning (DL). However, positive and negative effects have varied greatly among families, and the specific factors explaining these differences in experiences are still underexplored. In this study, we examined children’s executive functions (EF) and parents’ psychological well-being in relation to negative and positive effects of DL. Participants were 637 Italian parents (92%mothers) with a child (48%male) aged between 6 and 19 years involved in DL due to school closures during the first wave of the COVID-19 pandemic. Data were collected using an online survey. We performed three fixed‐order hierarchical multiple regression analyses with child age and sex, children’s EF deficits, and parents’ psychological well-being as independent variables, and DL-related negative effects and DL-related positive effects as dependent variables. The results of the regression analyses showed that for negative effects of DL, younger age and greater EF deficits explained most part of the variance. Specifically, regarding negative effects on children, the most important factor was EF deficits, whereas regarding negative effects on parents, child age was the most important factor. For positive effects of DL, all variables explained only a small part of the variance. Child age was the most important factor, but EF deficits and parents’ psychological well-being also had a significant impact. The effects of DL during school closures vary widely across families. Our findings indicate that intervention efforts need to consider background variables, child as well as parent factors when supporting families with homeschooling.